Relasi Kuasa dalam Novel Sunyi adalah Minuman Keras Karya Sapardi Djoko Damono: Analisis Wacana Kritis Michel Foucault - Abidin, Aslan; Ridwan, Ridwan; Saputra, Yusril (Belajar Bahasa: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study analyses Sapardi Djoko Damono's novel Sunyi adalah Minuman Keras (Silence is Alcohol), focusing on power relations over the body and mind, as well as forms of resistance that emerge in the text. This study aims to analyse Sapardi Djoko Damono's novel Sunyi adalah Minuman Keras (Silence is Alcohol), focusing on power relations over the body and mind, as well as forms of resistance that emerge in the text. Using a qualitative approach and Michel Foucault's critical discourse analysis, this study explains how power operates through language and shapes individual subjectivity in the novel. The results show that cognitive control mechanisms such as manipulation, objectification, and stigmatisation reflect power relations over the mind. These mechanisms shape the way characters view themselves and their world. Furthermore, social control that regulates physical actions, lifestyles, and bodily discipline reveals that power relations over the body are often reinforced by cultural and religious norms. The novel also depicts resistance to power through various explicit and implicit means in the characters' storylines. This study shows that Sunyi is Minuman Keras is not merely a work of literature, but also a complex representation of the power dynamics that shape human life. This study helps us understand how literary discourse can both replicate and challenge power structures in society.